DABIGATRAN AND DENTAL EXTRACTIONS - Case Report - Atanaska S. Dinkova; Dimitar T. Atanasov; Ludmila G. Vladimirova-Kitova (Peytchinski Publishing, 2017)
For more than 50 years, vitamin K antagonists have been the gold standard in the treatment of cardiovascular and cerebrovascular diseases and in the prevention of their complications. In the last 5 years new anticoagulants dabigatran, rivaroxaban and apixaban are rapidly implemented in the clinical practice, displacing Vit. K antagonists, due to numerous of advantages they have. Dabigatran is the first and most widely used new oral anticoagulant, so it is important for the dentists to be aware of this drug. The purpose of this article is to review NOA dabigatran, its monitoring and reversal, and provides clinical advice on the management of patients who receives dabigatran and requires dental extractions. Material and methods: The course of five patients on dabigatran who underwent teeth extraction was assessed. The medical charts of these patients were investigated. Morning dose of dabigatran (Pradaxa) was omitted and teeth extraction was performed ≥12 hours after the last intake of the drug. Results: Fourteen teeth were extracted in five patients receiving Dabigatran with normal creatinine clearance. Extractions were performed ≥12 hours after the last administration of dabigatran. Only one patient has slightly prolonged bleeding, successfully controlled with local hemostatic measures. Conclusions: Simple teeth extractions can be safely performed ≥12 hours after the last administration of the medication in patients with normal creatinine clearance without significantly greater bleeding risk than conventional oral anticoagulants. However, currently no established evidence-based guidelines for dental management of these patients are available and further clinical studies are needed.